“Nothing but Disgust” – Ladislav Klíma’s Connections with Gothicism - Goszczyńska, Joanna (Poznańskie Studia Slawistyczne, 2020)
Few interpretations of the work of Ladislav Klíma, by both Polish and Czech researchers, most often emphasize the philosophical aspect of his writing. They point to the connections of his work with the philosophy of Schopenhauer, Nietzsche, Berkeley. The article suggests taking a different lead related to connections with the Gothic Convention and the aesthetics of shock and disgust inscribed in it. The author used this convention, among others, to formulate his philosophy of Will. The article focuses on the mini-novel The Suffering of Prince Sternenhoch. The process of interpretation was facilitated by the use of findings of Jindřich Chalupecký, whereas the theories of Julia Kristeva proved useful in the methodological aspect.